2020
DOI: 10.14393/bj-v36n3a2020-42443
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chemical soil and corn yield after application of gypsum and potassium doses

Abstract: Soil liming is a common practice in agriculture. It aims to reduce soil acidity and to supply calcium and magnesium. Lime, however, is not easily soluble in the soil, and its reaction products are often concentrated in the application zone, which is mainly the topsoil layer. In order to increase the concentration of nutrients in deeper layers, agricultural gypsum—a byproduct of phosphoric acid production process, rich in calcium and sulfur—is used. In this context, the objective of this study was to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…Some crop yield responses to gypsum were detected in some sites, but the overall results indicated no significant differences between the gypsum sources and the untreated control. Additionally, Charlo et al (2020) reported that maize yield and plant biometric attributes were not influenced by gypsum or K 2 O doses; they also reported that gypsum caused cation (potassium and magnesium) displacement to deeper soil layers (0.2-0.4 m), which was not enough to improve maize responses.…”
Section: Less Expressive Gypsum Effectsmentioning
confidence: 99%
“…Some crop yield responses to gypsum were detected in some sites, but the overall results indicated no significant differences between the gypsum sources and the untreated control. Additionally, Charlo et al (2020) reported that maize yield and plant biometric attributes were not influenced by gypsum or K 2 O doses; they also reported that gypsum caused cation (potassium and magnesium) displacement to deeper soil layers (0.2-0.4 m), which was not enough to improve maize responses.…”
Section: Less Expressive Gypsum Effectsmentioning
confidence: 99%